Determination Of Perceived Barriers And Benefits Of Adopting Health-Promoting Behaviors In Cardiovascular Diseases Prevention: Application Of Preventative Behavior Model - Azar Tol; Sima Esmaeili Shahmirzadi; Davoud Shojaeizadeh; Mohamad Reza Eshraghian; Bahram Mohebbi (Tehran University of Medical Sciences, 2012)
Background and Aim: Cardiovascular diseases are the main cause of death and disabilities in the world. The purpose of the present study is to determine the perceived barriers and benefits of adopting health-promoting behaviors among individuals at risk of cardiovascular diseases referring to TUMS Teaching Hospitals in 2011. Materials and Methods: This is a cross-sectional study in which 325 patients at risk of cardiovascular diseases were randomly selected. The data were collected using a self-made questionnaire having three parts: 14 items for demographic and health-related variables, 12 items for perceived barriers, and another 12 items for benefits. For data analysis, SPSS 18 was used. Results: The mean age of patients was 53.56±11.27 about 47.7% of patients(n=155) were female and 52.3% (n=170) were male. There was a meaningful relationship between the mean of perceived benefits on the one hand and occupation, physical activity, type and frequency of physical activity, smoking and awareness of cardiovascular diseases on the other(p0.001). Moreover, the mean of perceived barriers showed a meaningful relationship with occupation, smoking and awareness of cardiovascular diseases(p0.05). Conclusion: The findings of the present study revealed that demographic and health-related variables could affect the perception of barriers and benefits of adopting certain behaviors for the prevention of cardiovascular diseases. Therefore, using interventional and educational approaches appropriate for target group features can help us take effective steps towards health promotion.